Comparison of circumferential peripheral angle closure using iridotrabecular contact index after laser iridotomy versus combined laser iridotomy and iridoplasty. Issue 7 (27th May 2017) - Cho, Hyun‐kyung; Kee, Changwon; Yang, Heon; Huh, Hyoun Do; Kim, Su Jin; Park, Young Min; Park, Jong Moon
Abstract: Purpose: To compare the quantitative changes of peripheral angle after laser iridotomy (LI) alone (group A) or combined LI and Iridoplasty (group B) using iridotrabecular contact (ITC) index by swept‐source anterior segment optical coherence tomography (AS‐OCT). Methods: In this prospective comparative observational study, OCT images were obtained before and after the procedure. In each image frame, scleral spur (SS) and the ITC end point (EP) were marked and ITC index was calculated as a percentage of the angle closure from 360°. Age, gender, diagnosis and initial ITC index in Group B were matched with group A. Changes in ITC index, anterior chamber angle parameters, and intraocular pressure (IOP) were inspected. Results: Thirty‐three eyes (20 patients) with shallow anterior chamber were included in each group. Initial ITC index and initial IOP were not significantly different between the two groups (both p   > 0.05). However, ITC index and IOP after the procedure were significantly lower in group B than those in group A (ITC index: 31.3 ± 23.2 in group A, 19.0 ± 21.3 in group B, p   =   0.011, IOP: p   =   0.004). All anterior chamber angle parameters in group B and all parameters in group A except nasal trabecular‐iris angles (TIA) were significantly increased after the laser procedure (all p   <   0.05). Conclusion: In patients with shallow anterior chamber, combined LI and Iridoplasty may open the peripheral angle better than LI alone. Iridoplasty may be able to additionally relieve the peripheral angle closure caused by other mechanisms than pupillary block.